2002
DOI: 10.1096/fj.02-0046com
|View full text |Cite
|
Sign up to set email alerts
|

A pivotal involvement of IFN‐' in the pathogenesis of acetaminophen‐induced acute liver injury

Abstract: In wild-type BALB/c mice, i.p. administration of acetaminophen (APAP; 750 mg/kg) induced intrahepatic IFN-gamma mRNA expression and a marked increase in serum transaminase levels, leading to acute lethality of approximately 45%. Histopathological examination showed centrilobular hepatic necrosis with leukocyte infiltration and a large number of apoptotic hepatocytes 10 and 24 h after APAP challenge. mRNA expression of intercellular adhesion molecule 1, vascular cell adhesion molecule 1, interleukin (IL) 1alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
233
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 205 publications
(246 citation statements)
references
References 32 publications
12
233
1
Order By: Relevance
“…We previously observed that the increases in serum ALT levels preceded neutrophil infiltration into liver in APAPinduced acute hepatotoxicity [13,14]. These observations raised questions on the pathogenic roles of neutrophil infiltration in APAP-induced liver dysfunction.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…We previously observed that the increases in serum ALT levels preceded neutrophil infiltration into liver in APAPinduced acute hepatotoxicity [13,14]. These observations raised questions on the pathogenic roles of neutrophil infiltration in APAP-induced liver dysfunction.…”
Section: Resultsmentioning
confidence: 98%
“…In line with this assumption, accumulating evidence has implicated neutrophils as the leukocyte type essentially involved in the pathogenesis of various liver diseases [8][9][10][11][12]. However, we previously observed that the increases in serum alanine transferase (ALT) levels preceded neutrophil infiltration into liver in APAPinduced liver injury [13,14]. Inactivation of neutrophils by anti-CD18 Ab had no effects on APAP-induced liver injury [15].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations